Colourful fun embroidery : featuring 24 modern projects to bring joy and happiness to your life! - Albans, Clare (White Owl, 2020)
Take time out to be creative and de-stress with these colourful, fun embroidery projects from Hello! Hooray! Ranging from things you could complete in an afternoon to others that you can take your time over, enjoy every step of the making process as you focus on feeling good through being creative. The finished makes will bring colour and joy to your home, workspace and wardrobe. The projects in this book allow you to craft your creative time by selecting makes according to timescale. Choose one of the 'crafternoon makes' if you want that sense of joy at finishing something, a 'medium makes' project for the days where you have a little more time for crafting, or for something to really take your time over you could stitch one of the longer 'pick me up' projects. Each project includes step-by-step instructions, beautiful photos and inspirational ideas for how to make each project your own. So take time to be creative with this colourful, feel-good craft book!